2017
DOI: 10.48550/arxiv.1705.06219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Largest acylindrical actions and stability in hierarchically hyperbolic groups

Abstract: We consider two manifestations of non-positive curvature: acylindrical actions (on hyperbolic spaces) and quasigeodesic stability. We study these properties for the class of hierarchically hyperbolic groups, which is a general framework for simultaneously studying many important families of groups, including mapping class groups, right-angled Coxeter groups, most 3-manifold groups, right-angled Artin groups, and many others.A group that admits an acylindrical action on a hyperbolic space may admit many such ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…We refer to [12,13,60] for definitions and background on hierarchically hyperbolic groups. What is relevant for us is that such groups share many properties with mapping class groups; in particular, a hierarchically hyperbolic group G admits an acylindrical action on a hyperbolic metric space X such that a subgroup H ≤ G is stable in G if and only if it is quasi-isometrically embedded in X under the orbit map [2]. We conjecture that the natural analogue of Theorem 1.7 also holds in this setting.…”
Section: Artin Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…We refer to [12,13,60] for definitions and background on hierarchically hyperbolic groups. What is relevant for us is that such groups share many properties with mapping class groups; in particular, a hierarchically hyperbolic group G admits an acylindrical action on a hyperbolic metric space X such that a subgroup H ≤ G is stable in G if and only if it is quasi-isometrically embedded in X under the orbit map [2]. We conjecture that the natural analogue of Theorem 1.7 also holds in this setting.…”
Section: Artin Groupsmentioning
confidence: 99%
“…In many cases when G is a group with an non-elementary partially WPD action on a hyperbolic metric space X, the subgroups of G which are quasi-isometrically embedded in X are precisely the stable subgroups of G in the sense of Durham-Taylor [2,7,24,40]. We prove an analogue of [49, Proposition 1] in the setting of a stable subgroup H of an acylindrically hyperbolic group G (Theorem 5.1).…”
Section: Introductionmentioning
confidence: 97%
“…After the first version of this preprint was made available, it has been brought to the author's attention that most of the results stated in Corollary C follow from the results in [Gen16,Gen18,GM18]. Moreover, a special case of Corollary D (when the vertex groups G v are hierarchically hyperbolic) follows from the results in [ABD17,BR18]. See Remarks 5.4 and 5.5 for details.…”
Section: Corollary D Let γ Be a Finite Simplicial Graph And Letmentioning
confidence: 99%
“…Moreover, the action of G on X induces an action of G on (a space quasi-isometric to) U = x∈X π S (x) ⊆ ĈS, and in [BHS17, Theorem 14.3] it is shown that this action is acylindrical. In [ABD17], this construction is modified so that the action G U represents the largest element of AH(G). If Γ is connected, non-trivial, and the groups G v are infinite and hierarchically hyperbolic (with the intersection property and clean containers), then the proof of Corollary D gives this action ΓG U explicitly.…”
Section: Ah-accessibilitymentioning
confidence: 99%
“…An acylindrical action of a group G on a hyperbolic metric space X is called universal [Osi16] if the elements of G that are loxodromic for this action are exactly the elements of G that are loxodromic for some acylindrical action of G on a hyperbolic space (such elements are called generalised loxodromic). Universal actions often offer much deeper insight into the structure of the underlying group, and are known to exist for instance for right-angled Artin groups [ABD17]. The goal of this article is to show the existence of such a universal acylindrical action for a large class of Artin groups, and to use the dynamics of the action to understand the structure of certain of its subgroups.…”
Section: Introductionmentioning
confidence: 99%